Analysis and Evaluation of 21st-Century Skills Integration in a Chapter of Grade IX Arabic Textbook for AFL - Uswah Mujahidah Rasuna Said; Asep Sopian; Aji Rizqi Ramadhan; Arina Dienana; Alfan Haidar (Arabiyatuna: Jurnal Bahasa Arab, 2026)
This study examines the integration of 21st-century skills in the Grade IX Arabic as a Foreign Language (AFL) textbook published by the Directorate of KSKK Madrasah, Directorate General of Islamic Education, Ministry of Religious Affairs of Indonesia. A qualitative descriptive design with an evaluative orientation was employed, focusing on Chapter 1, which covers texts, grammar, and learning tasks. The analysis was guided by the Partnership for 21st Century Learning (P21) framework, encompassing creativity and innovation, critical thinking and problem-solving, communication, and collaboration. Data were interpreted using a Likert scale. The findings indicate that creativity and innovation, as well as critical thinking and problem-solving, fall within the “sufficient” category (65–74), while communication and collaboration are classified as “outstanding” (85–100). These results reveal the textbook’s strength in promoting interaction and teamwork, while also highlighting gaps in fostering higher-order thinking and creativity. The implications underscore the need for a more balanced development of the four skill domains, suggesting that future textbooks should include more varied and challenging activities to promote creative exploration and critical engagement.